STEM-05. SINGLE CELL SEQUENCING CHARACTERIZES SPATIAL AND TEMPORAL RELATIONSHIPS OF ENHANCING AND NON-ENHANCING REGIONS IN HIGH-GRADE GLIOMA. (9th November 2020) - Patel, Kunal; Kawaguchi, Riki; Alvarado, Alvaro; Muthukrishnan, Deepthi; Everson, Richard; Liau, Linda; Geschwind, Daniel; Ellingson, Benjamin; Kornblum, Harley
Abstract: INTRODUCTION: Treatments of high grade glioma focus on the contrast enhancing (CE) portion of the tumor. However, given the invasive nature of glioma, residual tumor cells responsible for recurrence likely exist in the non-enhancing (NE) region. METHODS: In 3 patients undergoing surgery for malignant glioma, we used pre-operative magnetic resonance images to prospectively identify biopsy targets in the CE region and locations 0.5-2.0cm beyond the CE edge. We carried out single cell sequencing on image guided biopsy specimens to generate 12, 528 RNA profiles. RESULTS: In all samples, tumor cells clustered into three predominant groups: tumor cells with astrocyte markers (ASC-like), tumor cells with oligodendrocyte markers (ODC-like), and tumor cells with neither marker. This last group consisted of a small proportion of tumor cells and expressed putative stem cell markers (PROM1, NES, SLC1A3, A2B5, ID1). A trajectory analysis consistently positioned this group as branching off into either ASC-like or ODC-like cells. CE regions had different cellular compositions than NE regions, with higher proportions of tumor, endothelial cells, T-cells, and NK cells. Using location and cell density data, we modeled expected tumor burden, predicting tumor cells up to 1.5cm beyond the CE region of the tumor. There were significant differences in gene expression between CE and NE tumor cells, with increased inflammation and hypoxia in the CE region versus increased proliferative markers in the NE region. Tumor cells in the NE region were characterized by increased proliferation, markers of invasion, and markers of self-renewal. CONCLUSIONS: Single cell sequencing illustrates multiple glioma cell types and suggests a hierarchical relationship between tumor cell types. CE and NE regions exhibit different tumor and non-tumor cell populations as well as different gene expression profiles within individual cell types. There remains a significant tumor cell burden in the NE portion of tumor, including actively proliferating cells.